Urinary leucine aminopeptidase is a more sensitive indicator of early renal damage in non-insulin-dependent diabetics than microalbuminuria - (:unkn) unknown (KARGER, 1996)
We measured urinary activity of leucine aminopeptidase (EC 3.4.11.2) and creatinine concentrations (er, in mmol) in samples of second morning urine from 25 healthy subjects and 59 non-insulin-dependent diabetic (NIDD) subjects. If NIDD subjects are grouped according to their Alb/Cr ratio into normoalbuminuria (group A, Alb/Cr <2.8 mg/mmol), microalbuminuria (group B, Alb/Cr 2.8-26.8 mg/mmol), and macroalbuminuria (group C, Alb/Cr >26.8 mg/mmol), LAP/Cr ratios in all three groups exceeded those for healthy age-matched controls. Moreover, this ratio was higher in group B than in group A. The value for LAP/Cr was dearly abnormal (i.e., exceeded the upper limit of normal, log normal + 2 SD, found in healthy subjects) in 44% of group A. In the first 10-year period of NIDD, prevalance of abnormal LAP/Cr ratio was 61.3%, whereas that of microalbuminuria was 35.5%. We have also found a LAP/Cr ratio abnormality of 91% in group B. Evidently, LAP/Cr may be increased early in NIDD subjects and be a more sensitive predictor of incipient nephropathy than microalbuminuria.
Keywords: diabetes mellitus, non-insulin-dependent; diabetic nephropathies; leucine aminopeptidase; albuminuria; MELLITUS; ALBUMIN